2015
DOI: 10.1007/s11205-015-1176-2
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Poverty Index for Gauteng Province, South Africa: Evidence from Quality of Life Survey Data

Abstract: This paper estimates a Multidimensional Poverty Index for Gauteng province of South Africa. The Alkire-Forster method is applied on Quality of Life survey data for 2011 and 2013 which offer an excellent opportunity for estimating poverty at smaller geographical areas. The results suggest that the Multidimensional Poverty Index for Gauteng is low but varies markedly by municipality and by ward, as well as across income groups. Not only are low income households more likely to be multidimensionally poor, they al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 17 publications
(15 reference statements)
1
32
0
1
Order By: Relevance
“…The floor type and electricity access (only captured in 2011 and 2016 respectively) indicators are excluded from the MPI approach, but are replaced by dwelling type, overcrowding and refuse removal frequency indicators. The respective cut-off points for these indicators are as follows: residing at formal dwellings (same as StatsSA 2014); more than two persons per room (as adopted in Mushongera et al 2017;Omotoso & Koch 2017); less than once a week or no concrete refuse removal system (same as Adams et al 2015). Finally, asset ownership only takes television, landline telephone, cellular telephone, fridge, computer and radio into consideration as they are the only asset variables asked across all four datasets.…”
Section: Methodology and Data 31 Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The floor type and electricity access (only captured in 2011 and 2016 respectively) indicators are excluded from the MPI approach, but are replaced by dwelling type, overcrowding and refuse removal frequency indicators. The respective cut-off points for these indicators are as follows: residing at formal dwellings (same as StatsSA 2014); more than two persons per room (as adopted in Mushongera et al 2017;Omotoso & Koch 2017); less than once a week or no concrete refuse removal system (same as Adams et al 2015). Finally, asset ownership only takes television, landline telephone, cellular telephone, fridge, computer and radio into consideration as they are the only asset variables asked across all four datasets.…”
Section: Methodology and Data 31 Methodologymentioning
confidence: 99%
“…The later studies by Noble et al (2010) as well as Noble & Wright (2013), using the same data, adopted a similar approach to derive the index of multiple deprivation, but the former study focused on the Eastern Cape while the latter study examined the former homeland areas. Noble et al (2006Noble et al ( , 2010, Noble & Wright (2013), Burger et al (2017), Mushongera et al (2017) and StatsSA (2014StatsSA ( , 2017 are rare studies that examined multidimensional poverty by smaller geographical areas. Of these studies, StatsSA (2014) and Burger et al (2017) derived multidimensional poverty trends over time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have also used composite indices approach to develop national and provincial indices of multiple deprivation (Klaseen, 2000;Noble et al, 2006;Noble, Barnes, Wright, and Roberts, 2010). More recently, Finn et al, 2013;Woolard et al, 2013;Stat SA, 2014;Alkire and Santos, 2014;Ntsalaze and Ikhide, 2016;Mushongera et al, 2017;Frame et al, 2016;Rogan 2016;Pasha, 2016;OPHI, 2015;OPHI, 2017) have considered multidimensional poverty vis-a-vis gender dimension, youth dimension and cash grants at the national level using the Alkire and Foster (2011) technique and presenting mostly descriptive inferences. The Alkire and Foster MPI methodology has many advantages, which include its decompostional ability of helping to know how much each indicator and each dimension contributes to overall poverty and its ability to allow poverty comparisons across countries and regions of the world, as well as within-country comparisons between regions, ethnic groups, rural and urban areas, and other key household and community characteristics .…”
Section: Literature Reviewmentioning
confidence: 99%
“…This indicates that female headed households are significantly more likely to be multidimensionally poor than male counterparts. A spatial analysis of MPI in the Gauteng province of South Africa by Mushongera et al (2017) found out that low income earning households, poor accessibility to infrastructures and unemployment (as a result of low concentration of economic activities in specific locations) increases the likelihood of a household to be multidimensionally poor. Applying generalized additive model (GAM) using regression splines, Ntsalaze and Ikhide (2017) assessed the existence of critical tipping points specifically for age, government grants, education, household size and household debt service-to-income on multidimensional poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation